2004
DOI: 10.1124/jpet.104.067512
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of α-, β-, and γ-Cyclodextrins and Their Derivatives on an in Vitro Model of Blood-Brain Barrier

Abstract: Cyclodextrins (CDs) can be envisaged to cure some diseases related to the brain, but the behavior of these compounds toward the blood-brain barrier (BBB) remains largely unexplored to envisage such clinical applications. To fulfill this gap, the toxicity and endothelial permeability for native, methylated, and hydroxypropylated ␣-, ␤-, and ␥-CDs have been studied on an in vitro model of BBB. As shown by the endothelial permeability for sucrose and immunofluorescence stainings, the native CDs are the most toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 30 publications
6
52
0
Order By: Relevance
“…Because the BBB regulates the complex brain cholesterol homeostasis [38,39], it remains of interest to investigate how CD treatment may impact BBB cholesterol-depletion which in turn may influence ABCA1/G1 expression on brain cholesterol transport and synthesis. When toxicity was assessed, β-CD family (native, HPβCD and RAMEβ) was found more toxic than γ-CD family (native, HPγCD and RAMEγ) and less toxic than α-CD family (native, HPαCD and RAMEα) [34]. More recently, the cytotoxicity of β-CDs, HPβCD and TRIMETHYL-β-CDs has been investigated in a mouse model of immortalized cerebellum microvascular endothelial cells (cEND) and viability testing indicated the non-toxic effect of HPβCD as compared to the toxic β-CDs and TRIMETHYL-β-CDs [40].…”
Section: Direct Action Of the Cds On Cell Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the BBB regulates the complex brain cholesterol homeostasis [38,39], it remains of interest to investigate how CD treatment may impact BBB cholesterol-depletion which in turn may influence ABCA1/G1 expression on brain cholesterol transport and synthesis. When toxicity was assessed, β-CD family (native, HPβCD and RAMEβ) was found more toxic than γ-CD family (native, HPγCD and RAMEγ) and less toxic than α-CD family (native, HPαCD and RAMEα) [34]. More recently, the cytotoxicity of β-CDs, HPβCD and TRIMETHYL-β-CDs has been investigated in a mouse model of immortalized cerebellum microvascular endothelial cells (cEND) and viability testing indicated the non-toxic effect of HPβCD as compared to the toxic β-CDs and TRIMETHYL-β-CDs [40].…”
Section: Direct Action Of the Cds On Cell Membranesmentioning
confidence: 99%
“…Phospholipids, acting as acetylcholine precursor, would counteract the loss of cholinergic neurons responsible for impaired cognition in AD patients. The chitosan/phospholipid/β-CD microspheres were tested in vivo in rats modeling AD following Aβ [25][26][27][28][29][30][31][32][33][34][35] injection into the hippocampus. In these animals, learning and memory were improved according to Morris water maze test data compared to untreated littermates.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The insight of toxicity is probably related to interactions between CDs and membrane lipids. Indeed, as shown on our in vitro BBB model, γ-CD is able to extract cholesterol (13% compared to control) and phospholipids (20% compared to control) from BCEC membranes (Monnaert et al, 2004). Furthermore, a marked reduced toxicity for HP-γ-CD in comparison with γ-CD has already been described towards P388 murine leukaemia cells (Leroy-Lechat et al, 1994).…”
Section: Discussionmentioning
confidence: 73%
“…Published on as DOI: 10.1124 at ASPET Journals on May 12, 2018 jpet.aspetjournals.org Downloaded from JPET #71845 5 have described the behaviour of various CDs on an in vitro model of BBB (Monnaert et al, 2004). The γ-CD and hydroxypropyl-γ-CD (HP-γ-CD) have been found to be the less toxic CDs towards the brain capillary endothelial cells (BCEC) monolayer and were able to cross slightly the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…None of the data collected indicated that HP-β-CD enters the brain [21]. Other experiments examining cyclodextrins with regard to permeability using an in vitro model of the BBB have indicated that a small percentage of cyclodextrin may be transported across the barrier [22].…”
Section: Animal Studiesmentioning
confidence: 99%